Nanopartikel Sebagai Sistem Penghantaran Obat Tertarget Melalui Injeksi - Dikdik Caesar Barkah; Farid Ahmad; Dyanita Irene Susilo Putri; Siti Ningrum Ratna Ningsih; Nia Yuniarsih (JURNAL BIDANG ILMU KESEHATAN, 2023)
The pharmaceutical nanoparticles are in some way made with nanometers called nanometers or pharmaceutical substances encased in a nanometric system called nanocarrie. Targeted delivery systems are to increase drug dosage control at specific places such as in cells, tissues, or organs, and thus reduce unwanted side effects on non-target organs. So the riview journal is based on eight pharmacological activities of nanoparticles as a targeting drug delivery system of anti-cancer, antibacterial, immunomodulator, antiovarian, antifungal, antifungal, antibacterial, and antidiabetes Keywords: Nanoparticels, Drug Delivery System (DDS), Targeted delivery system, injection